Foreign students' experience in an online international market course in México - Díaz Gómez, Eduardo Raúl (My University, 2021)
This study involved 10 European undergraduate students enrolled in the online International Market Analysis (IMA) course offered through the International Business (IB) undergraduate program of CETYS Universidad. Using the Scholarship of Teaching and Learning (SoTL) theoretical approach and a qualitative research design, it asked how the students felt about their online educational experience. The results suggest that the students appreciated the freedom and flexibility that the online course provided. However, the lack of the physical presence of the teacher, and the challenges associated with working independently, made the learning experience less than optimal.
JEO the Journal of Educator on line
Keywords: SoTL; Online; Foreign students; Online perspective; Campus Ensenada